Flux growth of cubic boron phosphide crystals - Nwagwu, Ugochukwu; Edgar, James H.; Gong, Yinyan; Kuball, Martin (My University, 2013)
The ability to intercept attempts to smuggle nuclear weapons into the United States is critically important for homeland security. New types of neutron detectors are especially needed, as current devices employ a rare helium isotope (3He), which was a byproduct of the production of hydrogen bombs. As the production of nuclear weapons has largely ceased and the need for homeland security has grown, demand for 3He has greatly exceeded supply. Boron phosphide, BP, a compound semiconductor, is a potential alternative for neutron detectors because of the large thermal neutron capture cross-section of the boron-10 isotope (3840 barns). In this study, cubic BP crystals were grown by crystallizing dissolved boron and phosphorus from a nickel solvent in a sealed (initially evacuated) quartz tube. The boron - nickel solution was located at one end of the tube and held at 1150°C. Phosphorus, initially at the opposite end of the tube at a temperature of 430°C, vaporized producing a pressure of 1–5 atmospheres. Transparent red BP crystals, mostly hexagonal shape and up to 2mm in the largest dimension were obtained with a cooling rate of 3°C per hour, and less than 0.5mm with a cooling rate of 10°C per hour. The lattice constant of the crystals was 4.534Ǻ, as measured by x-ray diffraction. Intense, sharp Raman phonon peaks were located at 800cm-1 and 830cm-1, in agreement to values reported in the literature. Energy dispersive x-ray spectroscopy (EDS) and scanning electron microscope (SEM) also confirmed the synthesized crystals were cubic BP crystals, with boron to phosphorus atomic ratio of 1:1. Therefore, this flux growth method is capable of growing large, high quality BP crystals.
Keywords: boron phosphide; flux growth; boron monophosphide; solution growth; neutron detectors